Functional role of a novel algicidal compound produced by Pseudoruegeria sp. M32A2M on the harmful algae Alexandrium catenella. (August 2022) - Ko, So-Ra; Jeong, Yujin; Cho, Sang-Hyeok; Lee, Eunju; Jeong, Bo-Seong; Baek, Seung Ho; Oh, Byung-Ha; Ahn, Chi-Yong; Oh, Hee-Mock; Cho, Byung-Kwan; Cho, Suhyung
Abstract: A marine phytoplankton dinoflagellate, Alexandrium sp. is known to cause worldwide harmful algal blooms, resulting in paralytic shellfish poisoning. In this study, we isolated a novel compound secreted by the marine bacterium Pseudoruegeria sp. M32A2M, and showed that it displays algicidal activity against A. catenella (group I). The molecular structure of the compound was analyzed by using 1 H nuclear magnetic resonance (NMR), 13 C NMR, and gas chromatography-mass spectrometry, which revealed that the compound was a diketopiperazine, cyclo[Ala-Gly]. Cyclo[Ala-Gly] induced a rapid decrease in the active chlorophyll a content and maximal quantum yield of photosystem II, leading to membrane disintegration after 24 h of its treatment. It showed the highest algicidal effect against diketopiperazines and also showed specific algicidal activities against several dinoflagellate species, but not for diatom species. In particular, cyclo[Ala-Gly] caused the transcriptional downregulation of the photosynthesis-related membrane complex in A. catenella, but not in the diatom Chaetoceros simplex . Based on structural modeling, we elucidated that cyclo[Ala-Gly] has a structure similar to that of plastoquinone, which transfers electrons by binding to the photosystem II core proteins PsbA and PsbD. This suggests a novel role for cyclo[Ala-Gly] as a potential inhibitor of photosynthesis. Graphical abstract: Image 1 Highlights: A novel algicidal compound cyclo[Ala-Gly] was isolated from Pseudoruegeria sp. Cyclo[Ala-Gly] shows specific algicidal activity for several dinoflagellate. Cyclo[Ala-Gly] induces down-regulation of photosynthesis genes in A. catenella. Structure modeling suggests that cyclo[Ala-Gly] is an electron flow inhibitor.